Short-Term Outcomes of Transfemoral Carotid Artery Stenting and Carotid Endarterectomy in Symptomatic Patients: Data from a Multicentric Prospective Registry in Brazil - Joviliano, Edwaldo Edner; Ribeiro, Maurício Serra; Sobreira, Marcone Lima [UNESP]; Moura, Regina [UNESP]; Geiger, Martin Andreas; Guillamon, Ana Terezinha; Regina de Oliveira Raymundo, Selma; Miquelin, Daniel Gustavo; Hafner, Ludvig; Almeida, Marcelo Jose; Oliveira, Tércio Ferreira; Dalio, Marcelo Bellini; et al. (Elsevier, 2022)
Background: Transfemoral carotid artery stenting (TF-CAS) and carotid endarterectomy (CEA) are alternative strategies for stroke prevention in patients with atherosclerotic carotid disease. Because their main objective is to prevent future ischemic events, regular reassessment of the outcomes is mandatory for providing the best therapy. The purpose of this study was to describe the practice and the outcomes of TF-CAS and CEA in symptomatic patients in public university hospitals in Brazil, using data from a prospective multicentric registry. Methods: A prospective 8-year observational study of patients with symptomatic carotid artery atherosclerotic disease that underwent TF-CAS and CEA in 5 public university hospitals affiliated with the RHEUNI (Registry Project of Vascular Disease in the Public University Hospitals of São Paulo). All consecutive procedures were included. The indications for the procedures were determined by each surgeon's individual discretion, in accordance with a preoperative risk evaluation. The outcome measures were any 30-day follow-up death, stroke, myocardial infarction (MI), and their combined outcome (major adverse cardiovascular events [MACE]). The registration of the study was made at clinicaltrials.gov NCT02538276. Results: From January 2012 through December 2019, 376 consecutive and symptomatic patients were included in the study records. There were 152 TF-CAS procedures (40.4%) and 224 CEA procedures (59.5%). All completed the 30-day follow-up period. Occurrence of death (TF-CAS: 0.66% × CEA: 0.66%, P = 0.99), stroke (TF-CAS: 4.61% × CEA: 4.46%, P = 0.99), and MI (TF-CAS: 0.66% × CEA: 0%, P = 0.403) were similar in both groups, without statistically significant differences. MACE rate did not differ in both groups (TF-CAS: 5.92% × CEA: 4.46%, P = 0.633). Conclusions: Data from a prospective registry of 5 Brazilian university hospitals showed that TF-CAS and CEA in symptomatic patients had similar 30-day perioperative rates of death, stroke, and MI and their combination.